Genotypes of the mannan-binding lectin gene and susceptibility to visceral leishmaniasis and clinical complications - Alonso, Diego Peres; Ferreira, Afonso Flavio B.; Ribolla, Paulo Eduardo M.; Santos, Isabel K. F. de Miranda; Cruz, Maria do Socorro Pires e; de Carvalho, Fernando Aecio; Abatepaulo, Antonio Roberto Rodrigues; Costa, Dorcas Lamounier; Werneck, Guilherme L.; Farias, Teresinha J. C.; Soares, Maria Jose S.; Costa, Carlos Henrique N. (Univ Chicago Press, 2007)
Background. Visceral leishmaniasis (VL) is almost always lethal if not treated, but most infections with the causative agents are clinically silent. Mannan-binding lectin (MBL), an opsonin, is a candidate molecule for modifying progression to VL because it may enhance infection with intracellular pathogens. Mutations in the MBL2 gene decrease levels of MBL and may protect against development of VL. This case-control study examines genotypes of MBL2 and levels of MBL in individuals presenting with different outcomes of infection with Leishmania chagasi.Methods. Genotypes for MBL2 and levels of serum MBL were determined in uninfected control subjects (n=76) and in individuals presenting with asymptomatic infection (n=90) or VL (n=69).Results. Genotypes resulting in high levels of MBL were more frequent (odds ratio [OR], 2.5 [95% confidence interval {CI}, 1.3-5.0]; P=.006) among individuals with VL than among those with asymptomatic infections and were even more frequent (OR, 3.97 [95% CI, 1.10-14.38];P=.043) among cases of VL presenting with clinical complications than among those with uneventful courses. Serum levels of MBL were higher (P=.011) in individuals with VL than in asymptomatic infections.Conclusions. Genotypes of the MBL2 gene predict the risk for developing VL and clinical complications in infections with L. chagasi.